Properties of Arctic Aerosol Based on Sun Photometer Long-Term Measurements in Ny-Ålesund, Svalbard - Sandra Graßl; Christoph Ritter (Remote Sensing, 2019)
On the basis of sun photometer measurements located at the German-French polar research base AWIPEV in Ny-Ålesund ( 78.923 ° N, 11.928 ° E), Svalbard, long-term changes (2001–2017) of aerosol properties in the European Arctic are analyzed with the main focus on physical aerosol properties like Aerosol Optical Depth (AOD) and the Ångström exponent during the Arctic haze season in spring compared with summer and autumn months. In order to gain more information from the photometer data and to reduce the error of fitting the data to the Ångström law, a new approach with an Ångström exponent, which depends linearly on wavelength, is presented in this paper. With the Mie program of libRadtran, a calculator for long- and short-wave radiation through the Earth’s atmosphere, artificial aerosol size distributions were created to extend the physical understanding of this modified Ångström law. Monthly means of the measured AOD of the years 1994–2017 are presented to analyze long-term changes of aerosol properties and its load. Because photometer data in general have no height information, a comparison with a Lidar located at the same site is presented. The so-obtained data are then compared with the previous Mie calculus. More homogeneous aerosol properties were found during spring and more heterogeneous in summer. To study possible aerosol sources and sinks, five-day back-trajectories were calculated with the FLEXPART model at three different arriving heights at 11 UTC in the village Ny-Ålesund. Besides the pollution pathway of the aerosol into the European Arctic based on the calculated back-trajectories, the influence of the boundary layer parameterized by the lowermost 100 hPa atmospheric layer is analyzed and compared to the measured aerosol load by the photometer in Ny-Ålesund additionally. During spring, the open ocean acts as a sink for aerosols, whereas sea ice clearly reduces their sinks. Hence, trajectories over sea ice are correlated to higher aerosol loads. Thus, both sources and sinks must be considered to ...